KAJIAN BAURAN PEMASARAN PRODUK KOFFIE TANDJOENG DALAM MEMBANGUN BRAND AWARENESS DI KELOMPOK WANITA TANI (KWT) MEKAR ARUM - Alharitsza, Elshafira; Saidah, Zumi; Pardian, Pandi; Rochdiani, Dini (Universitas Galuh, 2023)
Koffie Tandjoeng is a local coffee brand from Sumedang that is produced by SME Mekar Arum Women Farmer Group. Efforts in to compete with other local coffee brands in the market, Koffie Tandjoeng needs to build its brand awareness with effective marketing activities. Marketing mix is a marketing tool that is used to create and build marketing activities effectively by identifying elements of marketing, which include product, price, place, and promotion. This study aims to identify the marketing mix of Koffie Tandjoeng, which is used in building brand awareness. This study uses a quantitative research design with a non-probability sampling technique, with 32 respondents determined by time linear function formulation. The results of this study show that consumers have a good response to product dimensions in product diversity, and price dimensions in the compatibility of the price and quality. Koffie Tandjoeng needs to improve its marketing activities in place and promotion dimensions in building brand awareness. The alternative suggestion to Koffie Tandjoeng in building brand awareness is to do a market expansion, maximizing the word-of-mouth promotion, promoting the products on social media, and promoting the products in events.